2021
DOI: 10.1161/circ.144.suppl_1.14009
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 14009: Longitudinal Analysis Supports Reproducibility Of Treatment With Sildenafil In The Semaxanib/Hypoxia Rat Model Of Pulmonary Arterial Hypertension

Abstract: Rats develop translatable pulmonary arterial hypertension (PAH) after exposure to the VEGF antagonist semaxanib (SU5416) concurrent with hypoxia. Sildenafil is used clinically for PAH and as a positive control in this preclinical model. A longitudinal analysis was constructed by pooling data from discrete rat PAH studies conducted over an 8-year period to evaluate the stability and reproducibility of the SU5416/Hypoxia rodent model as well as the response to sildenafil. Sprague-Dawley rats were administered SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this study, we used them as positive controls. Comparing with other anti-hypoxia drugs, such as dexamethasone and sildenafi, salidroside is considered to have lower toxic side effects and better tolerability [ 40 , 41 ]. Unfortunately, this study did not directly compare the difference in peptide LV efficacy with dexamethasone or sildenafi, but other researchers have found that salidroside is as effective as dexamethasone or sildenafil [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used them as positive controls. Comparing with other anti-hypoxia drugs, such as dexamethasone and sildenafi, salidroside is considered to have lower toxic side effects and better tolerability [ 40 , 41 ]. Unfortunately, this study did not directly compare the difference in peptide LV efficacy with dexamethasone or sildenafi, but other researchers have found that salidroside is as effective as dexamethasone or sildenafil [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with other anti-hypoxia drugs, such as dexamethasone and sildenafi, salidroside is considered to have lower toxic side effects and better tolerability [ 40 , 41 ]. Unfortunately, this study did not directly compare the difference in peptide LV efficacy with dexamethasone or sildenafi, but other researchers have found that salidroside is as effective as dexamethasone or sildenafil [ 40 , 41 ]. It suggests peptide LV may have resemble anti-hypoxia effect of dexamethasone or sildenafil, but putting them as direct control and additional studies in clinical trials is needed if peptide LV needs to further develop adjunct drug or functional food.…”
Section: Discussionmentioning
confidence: 99%
“…Different from reported approaches for BCB synthesis, this reaction proceeds smoothly at room temperature. To the best of our knowledge, this approach is the first case of the construction of BCBs via the light-catalyzed tandem reaction of 2-alkyl aromatic ketones and carbonyl compounds, and isatin is a widely employed building block for the synthesis of a wide variety of biologically active compounds, including clinically successful drugs, such as sunitinib, 34 semaxanib, 35 and toceranib. 36 We are convinced that this strategy not only showed a mild, clean, and economical method for the construction of BCBs but also presented application prospects in organic chemistry, such as the construction of organic compounds with complex structures.…”
mentioning
confidence: 99%